From biomimetics to smart materials and 3D technology: Applications in orthodontic bonding, debonding, and appliance design or fabrication - Theodore Eliades; Nearchos Panayi; Spyridon N. Papageorgiou (Elsevier, 2023)
This review covers aspects of orthodontic materials, appliance fabrication and bonding, crossing scientific fields and presenting recent advances in science and technology. Its purpose is to familiarize the reader with developments on these issues, indicate possible future applications of such pioneering approaches, and report the current status in orthodontics. The first section of this review covers shape-memory polymer wires, several misconceptions arising from the recent introduction of novel three-dimensional (3D)-printed aligners (mistakenly termed shape-memory polymers only because they present a certain degree of rebound capacity, as most non-stiff alloys or polymers do), frictionless surfaces enabling resistance-less sliding, self-healing materials for effective handling of fractured plastic/ceramic brackets, self-cleaning materials to minimize microbial attachment or plaque build-up on orthodontic appliances, elastomers with reduced force relaxation and extended stretching capacity to address the problem of inadequate force application during wire-engagement in the bracket slot, biomimetic (non-etching mediated) adhesive attachment to surfaces based on the model of the gecko and the mussel, and command-debond adhesives as options for an atraumatic debonding. This review's second section deals with the recent and largely unsubstantiated application of 3D-printed alloys and polymers in orthodontics and aspects of planning, material fabrication, and appliance design.